Berriasian–Valanginian Geochronology and Carbon-Isotope Stratigraphy of the Yellow Cat Member, Cedar Mountain Formation, Eastern Utah, USA - Robert M. Joeckel; Celina A. Suarez; Noah M. McLean; Andreas Möller; Gregory A. Ludvigson; Marina B. Suarez; James I. Kirkland; Joseph Andrew; Spencer Kiessling; Garrett A. Hatzell (Geosciences, 2023)
The Early Cretaceous Yellow Cat Member of the terrestrial Cedar Mountain Formation in Utah, USA. has been interpreted as a “time-rich” unit because of its dinosaur fossils, prominent paleosols, and the results of preliminary chemostratigraphic and geochronologic studies. Herein, we refine prior interpretations with: (1) a new composite C-isotope chemostratigraphic profile from the well-known Utahraptor Ridge dinosaur site, which exhibits δ13C features tentatively interpreted as the Valanginian double-peak carbon isotope excursion (the so-called “Weissert Event”) and some unnamed Berriasian features; and (2) a new cryptotephra zircon eruption age of 135.10 ± 0.30/0.31/0.34 Ma (2σ) derived from the CA-ID-TIMS U-Pb analyses of zircons from a paleosol cryptotephra. Our interpretations of δ13C features on our chemostratigraphic profile, in the context of our new radiometric age, are compatible with at least one prior age model for the “Weissert Event” and the most recent revision of the Cretaceous time scale. Our results also support the interpretation that the Yellow Cat Member records a significant part of Early Cretaceous time.